Effect of Lactate Minimum Speed-Guided Conditioning on Selected Blood Parameters of Horses - Santos, Maíra Moreira [UNESP]; Benvenuto, Guilherme Vechiato [UNESP]; Ramos, Gabriel Vieira [UNESP]; Titotto, Angélica Cristina [UNESP]; Adão, Milena dos Santos [UNESP]; de Lacerda, Luciana de Cenço Corrêa [UNESP]; Lisbôa, Júlio Augusto Naylor; Lacerda-Neto, José Corrêa de [UNESP] (Elsevier, 2022)
During exercise, equines can suffer severe water and electrolyte imbalances depending on the intensity and duration. In this sense, conditioning aims to promote adaptations to the organism in order to maintain cardiovascular and thermoregulatory stability during exertion. This study aimed to evaluate the effect of conditioning guided by lactate minimum speed (LMS) test on the blood osmolality of horses. We hypothesized that after conditioning the blood osmolality would vary less during exercise and that LMS could be used in equine conditioning program. Ten Arabian horses were evaluated before (ET 1) and after (ET 2) 6 weeks of conditioning. The conditioning intensity was established from the LMS during ET 1. The blood was obtained at rest and during the ETs. An increase in LMS and a decrease in lactate were seen in individual horses; however, these differences were not significant at a group level. No change in blood osmolality was observed when comparing the ETs. The plasma volume remained unchanged in ET 2. The conditioning guided by LMS improved the animals’ fitness, which was evidenced by the lower lactate production in ET 2. The fact that the osmolality kept unchanged proves the effectiveness of the osmotic blood balance during exercise, as its control involves the interaction of different systems. Body adaptations occurred with conditioning, providing greater homeostasis control since the plasma volume remained stable in ET 2. It was concluded that the LMS test can be used to define an effective equine conditioning program even though some adjustments are still necessary.
Keywords: Conditioning; Endurance capacity; Equine sports medicine; Exercise